Efektivitas Media Elektronik Interaktif Materi Pertumbuhan dan Perkembangan untuk Pembelajaran Siswa Sekolah Menengah - Eveline, Erlin; Permatasari, Rindah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Plant growth and development is one of the topics included in the current Indonesian education curriculum for Grade XII in senior high schools, and it is also known to be one of the challenging and difficult topics for students to understand. At present, there is no available learning media that adequately supports teachers in explaining this material optimally. Additionally, the time allocated for laboratory practicum activities is minimal. One of the media that can visualize the process of plant growth and development in a short amount of time is an interactive PowerPoint multimedia on the growth and development of lettuce (Lactuca sativa L..) through a floating raft hydroponic system. This study was conducted to evaluate the effectiveness of using interactive PowerPoint multimedia in teaching the topic of plant growth and development to Grade XII students in senior high school. The research was carried out in two stages. The first stage involved observing lettuce growth and development, conducted at Greenhouse Orchid Center in Pontianak. The second stage involved evaluating the effectiveness of the interactive PowerPoint multimedia by biology teachers from 12 senior high schools in Pontianak, using a closed questionnaire comprising seven criteria and 20 questions. The evaluation results showed that the interactive PowerPoint multimedia was highly effective (87.25%) and met all the predetermined criteria. Keywords: effectiveness, interactive powerpoint multimedia, growth, development, floating hydroponics, Lactuca sativa L..